2015
DOI: 10.17516/1997-1370-2015-8-8-1625-1634
|View full text |Cite
|
Sign up to set email alerts
|

Verbalization of the Writer in Academic Prose

Abstract: The paper presents an empirical analysis of the tools writers use to verbalize their stances in academic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…22 instances of first-person pronouns (1.32 p10kw) expressed this authorial role. This finding supports Krapivkina (2015), who reported that we is mostly used to mark the stance of a representative in research articles.…”
Section: Authors As Recounters Of the Research Processsupporting
confidence: 88%
See 1 more Smart Citation
“…22 instances of first-person pronouns (1.32 p10kw) expressed this authorial role. This finding supports Krapivkina (2015), who reported that we is mostly used to mark the stance of a representative in research articles.…”
Section: Authors As Recounters Of the Research Processsupporting
confidence: 88%
“…The presence of authors in scientific texts, especially research articles, has been investigated by a number of researchers (Hyland, 2002;2002b;2003;Dontcheva-Navratilova, 2013;Martin Martin, 2003;Hryniuk, 2018;Kuo, 1999;Krapivkina, 2015;Isler, 2018). In general, they examine the forms, or the grammatical aspects, as well as the functions of firstperson pronouns used in selected texts based on the criteria upon which each researcher decided.…”
mentioning
confidence: 99%
“…Based on frequency of linguistic features that indicate writer's stances, namely the researcher, the opinion holder, and the representative, O. Krapivkina compared papers written in English and in Russian. It was found that Russian authors preferred first-person plural pronouns, the third person and agentless passives while English language writers used both first-person singular and plural, agentless constructions, third person with human reference, and personified point of view constructions (Krapivkina, 2015). Although the studies mentioned provide some quantitative data and the results seem plausible, they can hardly be validated as the authors do not employ corpus methodology.…”
Section: Introductionmentioning
confidence: 95%
“…As expressions of authorial identities, first-person pronouns have been examined in various genres in such academic writing as research articles (e.g., Hyland, 2001;Işık-Taş, 2018;Sanderson, 2008), RA abstracts (Kim, 2015; Martí n Martí n, 2003), RA methods sections (Harwood, 2005b;Martinez, 2018), and theses (Hyland, 2002b;Isler, 2018;Karoly, 2009). Comparisons have also been attempted between the use of first-person pronouns in research articles written in English and those in Bulgarian, French, German and Russian (Vassileva, 1998), Croatian (Basic & Veselica-Majhut, 2016); French (Hartwell & Jacques, 2014), French, German and Italian (Rentel, 2012), German (Sanderson, 2008), Persian (Tayyebi, 2012), Polish (Hryniuk, 2018), Russian (Krapivkina, 2015), Spanish (Mur-Dueñas, 2011), and Turkish (Işık-Taş, 2018). These studies have shown that scientific disciplines (see, e.g., Harwood, 2005b;Hyland, 2001Hyland, , 2002a and writing cultures (see, e.g., Mur Dueñas, 2007; Mur-Dueñas, 2011; Vassileva, 1998) significantly affect the use of first-person pronouns as expressions of authorial identities.…”
Section: Authorial Identities In English Academic Discoursementioning
confidence: 99%